2018
DOI: 10.1007/s10439-018-02159-z
|View full text |Cite
|
Sign up to set email alerts
|

Mesh Convergence Behavior and the Effect of Element Integration of a Human Head Injury Model

Abstract: Numerous head injury models exist that vary in mesh density by orders of magnitude. A careful study of the mesh convergence behavior is necessary, especially in terms of strain most relevant to brain injury. To this end, as well as to investigate the effect of element integration on simulated strains, we re-meshed the Worcester Head Injury Model (WHIM) at five mesh densities (~7.2-1000 k hexahedral elements of the brain). Results from explicit dynamic simulations of three cadaveric impacts and an in vivo head … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 42 publications
(83 reference statements)
0
16
0
Order By: Relevance
“…Earlier studies have shown models with finer mesh would lead to large brain strains when other modeling parameter are the same. 27 , 53 Similarly, the variations in mesh density among the eight brain models may contribute to the difference in strain predictions. However, it is difficult to isolate and quantify the effect that the differences in numerical approaches has on the correlations between models and their rankings, because these factors are often interactive.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown models with finer mesh would lead to large brain strains when other modeling parameter are the same. 27 , 53 Similarly, the variations in mesh density among the eight brain models may contribute to the difference in strain predictions. However, it is difficult to isolate and quantify the effect that the differences in numerical approaches has on the correlations between models and their rankings, because these factors are often interactive.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have demonstrated that models with finer meshes would lead to the prediction of larger brain–skull relative motions and larger brain strains with the same set of material properties (Giudice et al. 2019 ; Zhao and Ji 2019a , b ). It is thus suggested that it may not be appropriate to adopt material properties of the brain obtained from a coarse mesh to a model with a much finer mesh, and vice versa (Zhao and Ji 2019a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…Continued efforts on model enhancement, including material model improvement, incorporating diffusion tensor imaging (DTI), brain–skull interface improvement, as well as mesh refinement, have led to updated versions compared to the original. Especially recent efforts on mesh refinement led to an average brain element size of about 1.8 mm in the WHIM V1.5 model (Zhao and Ji 2019a , b , 2020 ), while the element sizes in GHBMC (Mao et al 2013a ) and the refined THUMS (Atsumi et al. 2016 ) are also on the order of millimeter, being 2 mm, and 1.2 ~ 5 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For parametric studies, the model response has been evaluated using Pearson's correlation coefficient (r), linear regression slope (m), and correlation score (CS). Details of these measures can be found in Ganpule et al (2017) and Zhao and Ji (2019) and avoided here for brevity. Differences are considered to be statistically significant if one of the following conditions has been met.…”
Section: Discussionmentioning
confidence: 99%